2022
DOI: 10.3389/fcimb.2022.873416
|View full text |Cite
|
Sign up to set email alerts
|

Ferrets as a model for tuberculosis transmission

Abstract: Even with the COVID-19 pandemic, tuberculosis remains a leading cause of human death due to a single infectious agent. Until successfully treated, infected individuals may continue to transmit Mycobacterium tuberculosis bacilli to contacts. As with other respiratory pathogens, such as SARS-CoV-2, modeling the process of person-to-person transmission will inform efforts to develop vaccines and therapies that specifically impede disease transmission. The ferret (Mustela furo), a relatively inexpensive, small ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, in characterizing SARS-CoV-2 variants of concern, it provides an additional model to investigate in situ viral competition ( 327 ) showing that, for instance Omicron BA.1 was no longer able to replicate in the presence of evolving variants ( 328 ). Recent studies have reported that ferrets successfully transmit Mtb and develop TB pathology ( 295 ), thus extending the model value of ferrets also to a bacterial respiratory infection. Housing and handling ferrets in high-containment laboratories requires adequate training and space, making experimentation feasible only at selected institutions.…”
Section: Perspectivesmentioning
confidence: 92%
“…Moreover, in characterizing SARS-CoV-2 variants of concern, it provides an additional model to investigate in situ viral competition ( 327 ) showing that, for instance Omicron BA.1 was no longer able to replicate in the presence of evolving variants ( 328 ). Recent studies have reported that ferrets successfully transmit Mtb and develop TB pathology ( 295 ), thus extending the model value of ferrets also to a bacterial respiratory infection. Housing and handling ferrets in high-containment laboratories requires adequate training and space, making experimentation feasible only at selected institutions.…”
Section: Perspectivesmentioning
confidence: 92%